Supply chain management and logistics in Latin America : a multi-country perspective - Yoshizaki, Hugo; Velázquez Martínez, Josué C.; Mejía Argueta, Christopher (Emerald Publishing Limited, 2018)
Latin America is a well recognized and growing market, but its poor infrastructure, explosive urbanization, expensive and inefficient logistics, and multiple social problems continue to pose major problems to logistics professionals and academics. The uniqueness and complexity of these issues have long daunted scholars, and there remains an important gap in the literature around Latin American supply chain management and logistics (SCM&L).Supply Chain Management and Logistics in Latin America brings together leading scholars across Brazil, Colombia, Cuba, Ecuador, Peru, Panama, and the USA in order to address this gap. The chapters collected here, all of which are drawn from selected papers presented at the 2016 MIT SCALE Latin American Conference on Logistics and Supply Chain Management, offer perspectives from five different countries - Brazil, Colombia, Ecuador, Panama, and Peru - and provide insights into cases and new methods written by people who have faced the challenges they discuss. The authors cover a broad range of subjects: in addition to general contributions to qualitative and quantitative methods in supply chain management and coverage of cases of global importance such as the Panama Canal expansion, they offer insights into regionally specific problems around freight corridors in Colombia, reverse logistics and recycling in Colombia, supply risk management in Colombia, and socially oriented logistics in low-income communities in Peru. Since Latin America is one of the most urbanized regions in the world, with about eighty percent of the population living in cities, questions around urban logistics also receive heavy coverage, with four chapters discussing issues unique to very high-density cities and megacities such as São Paulo, Rio de Janeiro, Bogotá, and Quito.For its explorations of important themes, methods, and local topics within a crucial and ever-expanding market, Supply Chain Management and Logistics in Latin America is a valuable resource for educators, researchers, and practitioners.
Includes index.
Keywords: Business logistics -- Latin America -- Congresses.; Business & Economics -- International -- General.; Economics.; elektronické knihy; electronic books